Analisis Pendapatan Bersih Usaha Depot Air Minum Isi Ulang Agian Di Tenggarong - Anggareni, Aji Desilia; Suryadiansyah, Aji; Hayati, Nopi (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2018)
Abstract:The purpose of this study was to determine and analyze the amount of net income received by the Agian Water Refill Drinking business in Tenggarong between the researchers and companies.The data used are gross income, labor costs, operational costs and overhead costs for 2016 and 2017. The analytical tool used is quantitative analysis of cost accounting and profitability methods.Based on the results of research on the Water Depot for Agian refill in Tenggarong, the following conclusions can be drawn:1. In 2016 net profit margin obtained by Drinking Water Depot Agian refill for the researcher version was 35.79% and in the company version 40.90% with a difference of 5.11%. In 2017 both the researcher and company versions experienced a decline in value of 30.68% and 35.98% for the company version.2. In 2016 Total Assets Turnover produced by Drinking Water Depots by the researcher version of Agian refills is 1.35 times and the company version is 1.35 times or both calculations are the same. In 2017 the researchers version of the total assets turnover was 1.03 times and the company version 1.03 aka the same but the second value of this calculation decreased when compared to 2016.3. In 2016 Earning Power produced by Drinking Water Depot Agian refills the researcher version 49.02% and company version 56.01% with a difference of 6.99%. In 2017 the researcher version value was 32.20% and the company version was 37.75%, or there was a 173% decrease compared to Earning Power produced in 2016.4. In 2016 the Return On Investment (ROI) generated by the Drinking Water Depot Agian refills the researcher's version of 48.53% and the company version 55.45% with a difference of 7%. In 2017 the researcher version of the Return On Investment (ROI) value was 31.87% and the company version was 37.38%. From this value the two calculation versions in 2017 still experience a decline in value compared to 2016.5. In 2011 the Return On Equity produced by Drinking Water Depots by the researcher version of Agian refills was 72.84% and the company's version yield was 83.24%. For the 2017 version the researcher version is 37.59% and the entrepreneur's version is 44.07% or when compared the results of 2017 are still lower than in 2016.6. Based on the description, and see the results of the calculation, it can be concluded that the results of the calculation of the company's version of the analysis there are striking differences or still higher than the version of the researcher so that the hypothesis proposed earlier was accepted because it proved the truth.Â Keywords: Net Income